Menakar Undang-Undang Mineral dan Batubara terhadap Kerentanan Perlindungan Hak Masyarakat Hukum Adat - Ahsana Nadiyya; Ayu Putri Rainah Petung Banjaransari; Heni Rosida (CV Rewang Rencang, 2021)
The protection of indigenous peoples' rights conflicts with national law. This can be seen from the specifications of the Minerba Law which leave an important point for protecting the rights of indigenous peoples compared to their participation, such as the environmental impacts of mining activities. The Minerba Law is considered to have taken the space of indigenous peoples. The method used in this writing is juridical-normative. The recommendation of this research is the Bill on Customary Law Communities should be passed immediately since obtaining actual data from the territories and indigenous peoples regarding the protection of traditional rights. In addition, the government must also make implementing regulations starting from the central level to the regional level.